Validation of the Japanese version of the Chronic Liver Disease Questionnaire for the assessment of health‐related quality of life in patients with chronic viral hepatitis. Issue 3 (14th May 2015) - Tanaka, Atsushi; Kikuchi, Kentaro; Miura, Ryo; Miura, Kotaro; Mikami, Masaki; Aiso, Mitsuhiko; Takamori, Yoriyuki; Takikawa, Hajime
Abstract : Aim: Patients with chronic liver diseases (CLD) suffer from a variety of subjective symptoms, and the assessment of health‐related quality of life (HRQOL) is crucial. The Chronic Liver Disease Questionnaire (CLDQ) is the first liver disease‐specific instrument for this purpose. In this study we aimed to develop the Japanese version of CLDQ and to assess its validity and reliability in Japanese patients with chronic viral hepatitis. Methods: The participants included 135 Japanese patients chronically infected with hepatitis B or C virus. The Japanese version of the CLDQ was developed according to the standard "back‐translation" method. In addition to the Japanese version of the CLDQ, we asked the patients to fill out two other self‐report questionnaires: the Japanese versions of the 36‐Item Short Form Survey (SF‐36) and Hospital Anxiety and Depression Scale (HADS). Then, the internal consistency, convergent and discriminant validity of the Japanese version of CLDQ were statistically examined. Results: Cronbach's alpha of the Japanese version of the CLDQ was acceptable. The mean score was lower in emotional domains of the CLDQ, compared with those in somatic domains. Pearson correlations between Japanese CLDQ and SF‐36 and HADS were significant. The mean of the CLDQ scores decreased in all domains in patients with liver cirrhosis compared with those in patients with chronic hepatitis. Conclusion: The Japanese version of the CLDQ is a reliable and valid instrument for assessment of the HRQOL of Japanese patients with chronic viral hepatitis. The results also suggest that the HRQOL of Japanese patients is mainly impaired by emotional factors rather than somatic symptoms, and significantly worsened by progression of the disease.